2017
DOI: 10.3389/fpls.2017.01152
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single-Nucleotide Polymorphic Loci Associated with Biomass Yield under Water Deficit in Alfalfa (Medicago sativa L.) Using Genome-Wide Sequencing and Association Mapping

Abstract: Alfalfa is a worldwide grown forage crop and is important due to its high biomass production and nutritional value. However, the production of alfalfa is challenged by adverse environmental factors such as drought and other stresses. Developing drought resistance alfalfa is an important breeding target for enhancing alfalfa productivity in arid and semi-arid regions. In the present study, we used genotyping-by-sequencing and genome-wide association to identify marker loci associated with biomass yield under dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…Cutting frequently for high-quality forage always induce [19]. In previous study, we identified 22 markers associated with alfalfa yield under different water deficit conditions [20]. Of those, 15 markers were identical with the quality-related markers identified in this study, indicating that these loci might participate in controlling both the yield and quality traits in alfalfa.…”
Section: Discussionsupporting
confidence: 63%
“…Cutting frequently for high-quality forage always induce [19]. In previous study, we identified 22 markers associated with alfalfa yield under different water deficit conditions [20]. Of those, 15 markers were identical with the quality-related markers identified in this study, indicating that these loci might participate in controlling both the yield and quality traits in alfalfa.…”
Section: Discussionsupporting
confidence: 63%
“…Many of these loci were found to overlap with the reported QTLs associated with biomass yield under drought. Similar marker-trait associations have been identified for forage yield and nutritive value ( Sakiroglu and Brummer, 2017 ), forage quality traits ( Biazzi et al, 2017 ), plant growth and forage production ( Liu and Yu, 2017 ), and biomass yield under water deficit conditions ( Yu, 2017 ; Table 2 ). Thus, genetic dissection of forage-related traits using advanced approaches could be useful in identifying loci that can be exploited through marker-assisted breeding to develop drought-resistant alfalfa cultivars with improved nutritive value.…”
Section: Genetic Dissection Of Forage Traits In Legumessupporting
confidence: 61%
“…Several QTLs for important traits such as winter hardiness, fall growth and freezing injury ( Brouwer et al, 2000 ), biomass production ( Robins et al, 2007a ), forage yield ( Robins et al, 2007b ; McCord et al, 2014 ), plant height and regrowth ( Robins et al, 2007b ), persistence tolerance ( Robins et al, 2008 ) and, lodging resistance and spring vigor traits ( McCord et al, 2014 ) have been identified in tetraploid alfalfa ( Table 2 ). In addition, Ray et al (2015) identified small-effect QTLs controlling biomass yield under drought in tetraploid alfalfa ( Table 2 ).…”
Section: Genetic Dissection Of Forage Traits In Legumesmentioning
confidence: 99%
“…5. There are precedents for using FMY as a selection criterion in alfalfa ( Medicago sativa L.) breeding programs, either with an average DM adjustment from a small random sample of plots (Li et al, 2015) or without any DM adjustment (Yu, 2017). In perennial ryegrass ( Lolium perenne L.), FMY is routinely used as the principal selection criterion for forage yield plots under both conservation and frequent‐harvest managements, owing to relationships between FMY and DMY that are similar to those observed in the current study (Conaghan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%